Mechanical characterization of aluminum-silicon coating deposited by CVD-FBR on austenitic stainless steel AISI 316 and vapor oxidation (2018)
(Eng) Aluminum-Silicon Al-Si coating deposited at 540 °C on the austenitic stainless s teel AISI 316 by chemical vapor deposition in fluidized bed reactor (FBR-CVD), afterwards samples were thermally treated at 750 °C under argon for 2 hours. The coated samples were oxidized in water vapor loop at 750 °C, which showed a decrease in the corrosion rate at high temperatures in respect with the oxidized uncoated substrate (more than 100 times). Microhardness and nanoindentation studies were performed in order to assess the benefits of the Al-Si coating by CVD-FBR, finding an increase in the coating hardness with respect to the substrate. Additionally Scanning Electron Microscopy (SEM) was carried out to characterize micro-structural chang - es of the oxidized samples. Cross-section samples were subjected to Atomic Force Microscopy (AFM) fo - cusing on the thickness of coating (topographical changes, roughness gradient and possible formed phases). Results of AFM verified a correlation between hardness and voltages profiles found during scanning.